Study on the influence mechanism of perceived benefits on unsafe behavioral decision-making based on ERPs and EROs - Zhang, Shu; Yang, Qiyu; Wei, Cong; Shi, Xiuzhi; Zhang, Yan (Frontiers in Neuroscience, 2023)
Introduction Perceived benefits are considered one of the significant factors affecting an individual’s decision-making process. Our study aimed to explore the influence mechanism of perceived benefits in the decision-making process of unsafe behaviors. Methods Our study used the “One Stimulus-Two Key Choice (S-K1/K2)” paradigm to conduct an EEG experiment. Participants (N = 18) made decisions in risky scenarios under high perceived benefits (HPB), low perceived benefits (LPB), and control conditions (CC). Time domain analysis and time-frequency analysis were applied to the recorded EEG data to extract ERPs (event-related potentials) and EROs (event-related oscillations), which include the P3 component, theta oscillations, alpha oscillations, and beta oscillations. Results Under the HPB condition, the theta power in the central (p = 0.016*) and occipital regions (p = 0.006**) was significantly decreased compared to the CC. Similarly, the alpha power in the frontal (p = 0.022*), central (p = 0.037*), and occipital regions (p = 0.014*) was significantly reduced compared to the CC. Under the LPB condition, theta power in the frontal (p = 0.026*), central (p = 0.028*), and occipital regions (p = 0.010*) was significantly reduced compared to the CC. Conversely, alpha power in the frontal (p = 0.009**), central (p = 0.012*), and occipital regions (p = 0.040*) was significantly increased compared to the HPB condition. Discussion The high perceived benefits may reduce individuals’ internal attention and evoke individuals’ positive emotions and motivation, leading individuals to underestimate risks. Consequently, they exhibited a greater inclination toward unsafe behaviors. However, the low perceived benefits may reduce individuals’ memory review, resulting in a simple decision-making process, and they are more inclined to make fast decisions to avoid loss. The research results can help to provide targeted intervention measures, which are beneficial to reducing workers’ unsafe behaviors.